Identification of resilience factors, variables and indicators for sustainable management of urban drainage systems (2017)
Water management systems in general and urban drainage systems (UDS) in particular should be designed to ensure not only the provision of public service but also their sustainability and resilience. This paper performed an analysis and assessment to identify the factors, variables and indicators of resilience for sustainable UDS management by using an information management tool for scientific subjects. As a result of this analysis, four water resource resilience factors were identified: i. Flexibility; ii. Resourcefulness; iii. Redundancy; and iv. Robustness. In addition, six UDS resilience variables were identified: i. Recovery capacity; ii. Response capacity; iii. Amplitude; iv. Absorption capacity; v. Resistance capacity; and vi. Response curve. Corresponding indicators were proposed to quantify these variables. The identified elements contribute to the development of integrated frameworks to assess UDS resilience.